A Comprehensive Review of BET Protein Biochemistry, Physiology, and Pathological Roles - Ali, Hafiz Akbar; Li, Yalan; Bilal, Akram Hafiz Muhammad; Qin, Tingting; Yuan, Ziqiao; Zhao, Wen (Frontiers in Pharmacology, 2022)
Epigenetic modifications, specifically acetylation of histone plays a decisive role in gene regulation and transcription of normal cellular mechanisms and pathological conditions. The Bromodomain and extraterminal (BET) proteins, (BRD2, BRD3, BRD4 and BRDT) being epigenetic readers, ligate to acetylated regions of histone and synchronise gene transcription. BET proteins are crucial for normal cellular processing as they control cell cycle progression, neurogenesis, differentiation and maturation of erythroids and spermatogenesis etc. Research-based evidence indicated BET proteins (mainly BRD4) are associated with numeral pathological ailments, including cancer, inflammation, infections, renal diseases and cardiac diseases. To counter the BET proteins related pathological conditions, there are some BET inhibitors developed and also under development. BET proteins are a topic of most research nowadays. This review, provide an ephemeral but comprehensive knowledge about BET proteins’ basic structure, biochemistry, physiological roles and pathological conditions in which the role of BETs have been proven. This review also highlights the current and future approaches to pledge BET proteins related pathologies.